Perspektif Pendidikan Islam Dalam Novel Dan Damai Di Bumi! Karya Karl May - Ma’rifah, Indriyani (Jurnal Pendidikan Islam, 2012)
Conflict and violence based on ethnic, religion, race and inter-groups (SARA) still become an inherent part of the historical life for Indonesian people. It is quitely clear that the Islamic education has not been effective enough to instill values of peace. Therefore, the reconstruction and renewal of the Islamic education should be done. It is necessary for us to begin with the reconstruction of the learning materials, and by using the novel as a medium. One of the novels that is loaded with the values of peace is “Dan Damai di Bumi!“ written by Karl May